Amyloidosis, Inflammation, and Oxidative Stress in the Heart of an Alkaptonuric Patient. (28th April 2014) - Millucci, Lia; Ghezzi, Lorenzo; Paccagnini, Eugenio; Giorgetti, Giovanna; Viti, Cecilia; Braconi, Daniela; Laschi, Marcella; Geminiani, Michela; Soldani, Patrizia; Lupetti, Pietro; Orlandini, Maurizio; Benvenuti, Chiara; et al.
Abstract : Background . Alkaptonuria, a rare autosomal recessive metabolic disorder caused by deficiency in homogentisate 1, 2-dioxygenase activity, leads to accumulation of oxidised homogentisic acid in cartilage and collagenous structures present in all organs and tissues, especially joints and heart, causing a pigmentation called ochronosis. A secondary amyloidosis is associated with AKU. Here we report a study of an aortic valve from an AKU patient. Results . Congo Red birefringence, Th-T fluorescence, and biochemical assays demonstrated the presence of SAA-amyloid deposits in AKU stenotic aortic valve. Light and electron microscopy assessed the colocalization of ochronotic pigment and SAA-amyloid, the presence of calcified areas in the valve. Immunofluorescence detected lipid peroxidation of the tissue and lymphocyte/macrophage infiltration causing inflammation. High SAA plasma levels and proinflammatory cytokines levels comparable to those from rheumatoid arthritis patients were found in AKU patient. Conclusions . SAA-amyloidosis was present in the aortic valve from an AKU patient and colocalized with ochronotic pigment as well as with tissue calcification, lipid oxidation, macrophages infiltration, cell death, and tissue degeneration. A local HGD expression in human cardiac tissue has also been ascertained suggesting a consequent local production of ochronotic pigment in AKU heart.